A Multicentral Quasi experimental Study on Impact of Neuromuscular Taping over Low Back Pain - Yu Chye Wah1 , Kshtrashal Singh2 , Susmitha Govind3 , Kasmalina binti Mohd4 , Siva Sangary Murthy5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Low back pain in particular is considered to one of the major health problem in modernsocieties. It is also increasing in intensity, frequency, and severity because of more stress and strain onthe back and. chronic lower back pain patient uses the health care system twice as often as the rest of thepopulation. Objective: This study is done to check the effectiveness of Neuromuscular Taping over LowBack Pain in collaboration with Aimst University (Malaysia), NMT Institute Italy & USA, University ofIndonesia, Mekelle University Ethiopia & Institute of Paramedical Sciences, Kannur, India. Methodology:A qualitative research model in the form of a prospective type quasi experimental study design is carriedout in this study. The study is conducted in collaboration with AIMST University Malaysia, Universityof Indonesia, NMT Institute Italy & USA, Institute of Paramedical Sciences, Kannur, India and MekelleUniversity Ethiopia. Conveniently 800 Participants were selected in collaboration with AIMST UniversityMalaysia, University of Indonesia, NMT Institute Italy & USA, Mekelle University Ethiopia & Institute ofParamedical Sciences, Kannur, India. Result: All selected Participants with Low back pain symptoms wereassessed for low back pain index (LBPI) respectively before and after intervention with neuromusculartaping. The results from most of the participants showed significantly improvement after intervention.Conclusion: In this study pain factor is reducing, considering the fact NMT can be included as one amongthe modality used for the Treatment of Back Pain. Introduction of new intervention such as neuromusculartaping in terms of back pain Management itself is a very challenging. The investigation of such studies andtheir result will help for further research prospective.